2018
DOI: 10.1111/apa.14356
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence of thinness, overweight and obesity among Swedish children and adolescents between 2004 and 2015

Abstract: The prevalence of obesity decreased from 2004 to 2015 or was stable in younger Swedish children, but increased among older children, with a large increase in adolescent boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
6
23
1
Order By: Relevance
“…29 30 In our data, boys were more often obese than girls, in general, which was in agreement with previous Chinese reports. [30][31][32] A Swedish report 33 predicted that there was an alarming increase in the prevalence of overweight and obesity among adolescent boys, which was consistent with our finding. On the one hand, in traditional Chinese culture, the preference for boys may be the reason for the differences in diet, and the elderly believe that fat boys are more powerful than thin boys.…”
Section: Discussionsupporting
confidence: 92%
“…29 30 In our data, boys were more often obese than girls, in general, which was in agreement with previous Chinese reports. [30][31][32] A Swedish report 33 predicted that there was an alarming increase in the prevalence of overweight and obesity among adolescent boys, which was consistent with our finding. On the one hand, in traditional Chinese culture, the preference for boys may be the reason for the differences in diet, and the elderly believe that fat boys are more powerful than thin boys.…”
Section: Discussionsupporting
confidence: 92%
“…This study finds that patients with a history of SCFE have a 9-fold higher risk of being diagnosed with obesity than their age-and sex-matched controls, with a higher risk for male patients. Over time, the prevalence of obesity in children has increased in both sexes (Eriksson et al 2018). Perry et al (2018) found a strong association of BMI and SCFE, with a higher risk for SCFE in children with obesity and high BMI compared with children of normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Fate of patients with slipped capital femoral epiphysis (SCFE) in later life: risk of obesity, hypothyroidism, and death in 2,564 patients with SCFE compared with 25,638 controls Slipped capital femoral epiphysis (SCFE) occurs commonly in overweight children and adolescents. The etiology of the disease is still unknown but several studies have concluded that overweight and obesity are catalyzing factors, either by overloading the growth plate (Fishkin et al 2006) or as an endocrine condition diminishing the stability of the growth plate. The latter would explain the age-dependent relationship between obesity and SCFE onset, where obese children are found to suffer from SCFE at a younger age compared with children of age-and length-adequate weight (Perry et al 2018).…”
mentioning
confidence: 99%
“…We had no information on the weight and height of the children in the comparison group, nor on the parents. The prevalence of obesity in individuals aged 7 to 17 years in Sweden is estimated to somewhere between 4 and 8% [44]. Thus, we cannot rule out that there are individuals with obesity in the comparison group.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 94%